OPTIMALISASI BRANDING IMAGE PENDIDIKAN NONFORMAL DALAM MENINGKATKAN KEPERCAYAAN MASYARAKAT (STUDI KASUS DI PONDOK PUTRI RIDWAN ANWARUL HALIMY) - Kholisussa'di; Herlina; Rila Hardiansyah (Comm-Edu (Community Education Journal), 2026)
Pondok Putri Ridwan Anwarul Halimy is one of the non formal educational institutions dedicated to students and has instilled Islamic values, discipline, and leadership in every learning process. The purpose of this research is to describe the branding image strategy applied at Pondok Putri Ridwan Anwarul Halimy, identify the factors that affect the formation of the institution's image in the community, Analyze The Influence of Branding Image on the Level of Public Trust. The research method used in this study is a qualitative research method. The results of the study are that the branding image of the pondok appears in four main dimensions: (1) value branding, through the cultivation of sincerity, discipline, simplicity, and leadership; (2) visual and symbolic identity, through sharia uniforms, institutional attributes, and religious spatial planning; (3) flagship programs as core products, such as tahfidz, the yellow book, foreign language habituation, and leadership coaching; and (4) relational branding, through active involvement in the socio religious activities of the community. Optimizing the branding image of Pondok Putri Ridwan Anwarul Halimy contributes significantly to building and maintaining public trust, as well as becoming a relevant image management model for other Islamic based non formal educational institutions.